The existence of village regulations for development community empowerment in Padang village Polewali Mandar regency - Eka Dewi Kartika; Fadli Yasser; Salma Laitupa (Indonesia Prime, 2021)
The goal of accelerating the welfare of the people faster through village regulations can be seen by setting village regulations that are right on target for village community empowerment, such as village regulations on village potential development, for increasing village income as a form of village community empowerment in Padang village there is only a village regulation on village budgets, which is indeed an obligation in the village government budget and spending arrangements. Every year and the village regulations tentag farm animals.The lack of village regulation documents, which should be made to be the legality of every policy and action taken by the Village government and for welfare, environmental order, empowerment will have implications in the inaccuracy of the development of village community empowerment that has been mandated in the VillageLaw. Methods using a statutory research approach and a concept of approach that then uses the nature of quantitative research and qualitative descriptions. The existence of village regulations that are expected to be regulations that make the direction of the village government system in Padang village does not run optimally with a lack of knowledge from village officials and village consultative bodies for their duties and work functions thus the lack of village regulation documents in Padang village has implications for inequality. Government administaris and programs that do not have legal protection and are not targeted in the empowerment of rural communities. We recommend that padang villages and other villages that are aware of the lack of village regulation regulations, should establish cooperation relations with the university in providing village rule-making training in accordance with the cultural environment, village community in terms of village community empowerment and socialization about the implementation of good village governance